Aptitude for Destruction, Volume 1 Organizational Learning in Terrorist Groups and Its Implications for Combating Terrorism - Jackson, Brian A. (RAND Corporation, 2005)
Better ways are needed to understand how terrorist groups become more effective and dangerous. Learning is the link between what a group wants to do and its ability to actually do it; therefore, a better understanding of group learning might contribute to the design of better measures for combating terrorism. This study analyzes current understanding of group learning and the factors that influence it and outlines a framework that should be useful in present analytical efforts and for identifying areas requiring further study.